Aspek Kebencian dan Kehormatan dalam Puisi Perang antara Belanda dan Aceh - Harun, Mohd (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The study examines war poems between the Dutch and Aceh in terms of hatred and honor. The data on the war poems were obtained from written sources produced by both the Dutch and the Acehnese. The data were analyzed using a sociology of literature approach. The results of the study show that: (1) the Dutch’s hatred toward Aceh, which was labelled as the den of criminals, traitor, and anathema, was implanted before the aggression through poems sung by the military personnel sent to Aceh; (2) the Acehnese’s hatred toward Kaphe Belanda (Dutch infidels), who were labelled as heretic infidels, maledict infidels, cursed infidels, and Jewish infidels, was implanted through war poems that inspired the Acehnese to willingly die in battles against the Dutch wherever they were, whether during wartime or periods of ceasefire; (3) for the Dutch, fighting against Aceh was a means of defending the honor of the motherland and obtaining medals of honor; and (4) for the Acehnese, fighting against the Dutch was a collective obligation, and dying as a martyr in a holy war represented the highest honor of being Acehnese.